Analysis of Factors and Indicators Influencing Human Error Reduction in Construction Projects: Analisis Faktor dan Indikator yang Mempengaruhi Penurunan Human Error pada Proyek Konstruksi - Cynthia Fadhila Diantoro Putri; Mohammad Arif Rohman (Universitas Negeri Surabaya, 2026)
Human error remains one of the leading causes of accidents in construction projects due to the complexity of work activities, dynamic working conditions, and various hazards present on construction sites. Safety knowledge, safety skills, and the work environment are recognized as important factors in reducing human error. However, studies that integrate these factors into a single validated framework remain limited. This study aims to identify and validate the factors and indicators influencing human error reduction in construction projects. Data were collected through questionnaire surveys administered to Occupational Safety and Health (OSH) personnel working in construction companies in Indonesia and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results identified four key factors, namely safety knowledge, safety skills, work environment, and human error reduction, represented by 17 valid and reliable indicators. The findings indicate that safety knowledge, safety skills, and the work environment contribute significantly to reducing human error in construction projects. This study provides an empirically validated framework of factors and indicators to support the development of safety management strategies aimed at reducing human error and improving safety performance in construction projects.